PEMBENTUKAN DANA WAKAF MENURUT PERSPEKTIF SYARIAH DAN UNDANG-UNDANG SERTA APLIKASINYA DI MALAYSIA - Mahamood, Siti Mashitoh (Jurnal Syariah, 2019)
This article discusses the establishment of a wakaf fond in Malaysia within Syariah and current legal perspectives. The various contemporary modes of creating wakaf and its financial development are highlighted including wakaf shares, cash wakaf, WakafTakafol Plan (Pelan Takafol Wakaj), wakaf of sukuk or Islamic bond, wakaf REIT and others. The author also suggests the establishment of a National Wakaf Fund (Dana Wakaf Kebangsaan) which can benefit the nation, particularly the wakaf beneficiaries.